Multicenter benchmarking of short and long read wet lab protocols for clinical viral metagenomics - Lopez-Labrador, F Xavier; Huber, Michael; Sidorov, Igor A; Brown, Julianne R; Cuypers, Lize; Laenen, Lies; Vanmechelen, Bert; Maes, Piet; Fischer, Nicole; Pichler, Ian; Storey, Nathaniel; Atkinson, Laura; et al. (Journal of clinical virology, 2024)
Metagenomics is gradually being implemented for diagnosing infectious diseases. However, in-depth protocol comparisons for viral detection have been limited to individual sets of experimental workflows and laboratories. In this study, we present a benchmark of metagenomics protocols used in clinical diagnostic laboratories initiated by the European Society for Clinical Virology (ESCV) Network on NGS (ENNGS). A mock viral reference panel was designed to mimic low biomass clinical specimens. The panel was used to assess the performance of twelve metagenomic wet lab protocols currently in use in the diagnostic laboratories of participating ENNGS member institutions. Both Illumina and Nanopore, shotgun and targeted capture probe protocols were included. Performance metrics sensitivity, specificity, and quantitative potential were assessed using a central bioinformatics pipeline. Overall, viral pathogens with loads down to 104 copies/ml (corresponding to CT values of 31 in our PCR assays) were detected by all the evaluated metagenomic wet lab protocols. In contrast, lower abundant mixed viruses of CT values of 35 and higher were detected only by a minority of the protocols. Considering the reference panel as the gold standard, optimal thresholds to define a positive result were determined per protocol, based on the horizontal genome coverage. Implementing these thresholds, sensitivity and specificity of the protocols ranged from 67 to 100 % and 87 to 100 %, respectively. A variety of metagenomic protocols are currently in use in clinical diagnostic laboratories. Detection of low abundant viral pathogens and mixed infections remains a challenge, implying the need for standardization of metagenomic analysis for use in clinical settings.
Keywords: Computational Biology; benchmarking; vysoce účinné nukleotidové sekvenování; lidé; senzitivita a specificita; výpočetní biologie; Sensitivity and Specificity; High-Throughput Nucleotide Sequencing; virové nemoci; Viruses; Humans; viry; Virus Diseases; Metagenomics; metagenomika; Benchmarking